Changes to coping and its relationship to improved wellbeing in the optimal health program for chronic disease - Maya S. Sheth; David J. Castle; Wei Wang; Alina Lee; Zoe M. Jenkins; Lisa D. Hawke (Elsevier, 2023)
Background: Adaptive-style coping strategies are associated with favourable mental health and quality of life outcomes among individuals with chronic disease. The Optimal Health Program (OHP) is a psychosocial self-efficacy program that empowers individuals to be active leaders in their health and wellness management. This study aimed to evaluate the impact of the OHP on coping styles. Methods: Adults with Type 1 or Type 2 diabetes, chronic kidney disease, stroke survivors, and stroke carers were recruited from St. Vincent's Hospital, Australia, to participate in one of three trials evaluating the efficacy of the OHP compared to usual care for the management of these chronic conditions. Coping was assessed at baseline, then at 3, 6- and 12-months post baseline. To examine changes in coping in association with OHP participation, we conducted a linear mixed-effects model, using the repeated measures approach. Results: The sample was comprised of 411 participants, with 76 (18.5%) stroke survivors, 69 (16.8%) stroke carers, 151 (36.7%) chronic kidney disease patients, and 115 (28.0%) diabetes mellitus patients. There were significant group by time interactions for problem-focused coping, instrumental support, positive reframing, and self-blame, indicating that participants in the OHP arm improved significantly more than those in the control group with regard to coping styles. Many interactions were significant at 3 and 6 months, but not 12 months. Conclusion: The OHP was successful in improving adaptive coping behaviours and decreasing maladaptive coping behaviours in the short-term, but the effects were not maintained at 12 months. Additional booster sessions may be helpful in sustaining intervention effects. This study serves as support for the importance of interventions targeting the psychosocial and physical health aspects of chronic disease to improve individuals' overall wellbeing.